2002
DOI: 10.1021/jp0123684
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Probing of a 2c/3e Disulfide Bond Making in Liquid Phase

Abstract: The subpicosecond ultraviolet observation of a sulfur−sulfur bond making (2σ/1σ* bond) is carried out in pure liquid dimethyl sulfide at 294 K. The early stages of a disulfide bonded radical formation (CH3S∴SCH3 -) are characterized by a nonlinear λ max red shift of the absorption spectrum. In the temporal range 0−1600 fs, the red shift of 0.31 ± 0.1 eV is analyzed in the framework of a change of the 2σ/1σ* transition due to a lowering of the 2c,3e S−S bond strength and/or a destabilization of the σ lone pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Until now, the sulfur–sulfur hemi-bond has been characterized only by EPR and UV-vis (transient) absorption. 16 18 However, it is very difficult to directly extract structural information from these types of experiments. Spectroscopic evidence in the gas phase has been highly requested to examine the theoretical predictions of the sulfur–sulfur hemi-bond.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the sulfur–sulfur hemi-bond has been characterized only by EPR and UV-vis (transient) absorption. 16 18 However, it is very difficult to directly extract structural information from these types of experiments. Spectroscopic evidence in the gas phase has been highly requested to examine the theoretical predictions of the sulfur–sulfur hemi-bond.…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively studied group is that of sulfur-centered radical cations, but they can also be found in anions [7,21,25,26,29] or neutrals adducts [24,27,28,30,36]. Time-resolved pulse radiolysis techniques have demonstrated that particularly the sulfur-containing species exhibit strong optical absorption in the visible and near UV regions.…”
Section: Figurementioning
confidence: 99%
“…For instance, the dramatic lengthening of the intersulfur distance (ca. 0.7 Å) can be monitored by femto-second laser photochemistry [7] or visualized on Fourier maps of a X-ray irradiated disulfide-linked enzyme [4]. Exploitation of these data is intrinsically delicate, and certainly benefits from the complementary perspective offered by ab initio approaches [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Emphasis was recently given to the formation [28,29] and UV/ vis signature of disulfide radical anions [7,6], by contrast with their dissociation, for which a correction has been proposed [30]. Such an analysis involves three relevant descriptors: adiabatic electron affinity (AEA), inter-sulfur distance d SS , and longest wavelength of maximal absorption k max .…”
Section: Introductionmentioning
confidence: 99%